Research on Dynamic Characteristics and Compensation of Wire Rope Tension and Load Measurement Based on Hydraulic Connection Device. (16th May 2019) - Song, Di; Xu, Gui-Yun; Lei, Gao-Yang; Zhang, Xiao-Guang; Tian, Bao-Lai
Abstract : During the operation of hoist, the speed and acceleration of each wire rope are inconsistent and the inertia force is changed due to the wear of the friction pad on the drum, which makes an impact on the cylinder of the tension balance hydraulic connection device and aggravates the flow pressure loss. It results in the nonlinear friction force between the piston and cylinder and affects the accuracy of wire rope tension and load measured by an oil pressure sensor which is installed on the tension balance hydraulic connecting device. In this paper, the simulation model of the tension balanced hydraulic connecting device is established by AMESim software, and the hydraulic dynamic response under different pressures, flow rates, and speed of a single hydraulic cylinder and tension balanced hydraulic connecting device is analyzed. The Leuven friction model is used to compensate the pressure loss along the course and local pressure loss and calculate the friction force, where specific parameters are determined by experiments. The real-time compensation experiment of the tension balance hydraulic connecting device proves that the device effectively improves the accuracy of wire rope tension and load monitoring.